Budaya Organisasi Pascapengembangan dengan Pendekatan Manajemen Berbasis Sekolah - Rusdinal Rusdinal (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2006)
The focus of this study is to describe the organization atmosphere of school institutions after an organization-development program adopting school-based management approach. This qualitative study involved three elementary schools, utilizing multi-site design and constant-comparative method. The data were collected through participatory observation, in-depth interviews, documentation. The results of descriptive analyses show that the program offered positive effects on building up the institution culture. The headmasters played important roles in norm and value enforcement. The teachers became committed to the best achievement and sense of belonging. The spirit of togetherness thus developed well at the schools.